Numerical Simulation of Oil Pipeline Leakage Diffusion in Dashagou Yellow River Crossing Section - Shaokang Liu; Mingyang Qiu; Guizhang Zhao; Menghan Jia; Jie An; Xi Guo; Dantong Lin; Yangsheng Tian; Jiangtao Zhou (Applied Sciences)
In this study, the ANSYS 2020R1 software simulation is employed to examine the diffusion process of oil leakage and the underground water solute transport law in the Dashagou Yellow River crossing section of the oil pipeline. The simulation results demonstrate that under identical leakage pressure conditions, diesel fuel leakage in powdery, sandy soil is diminished, the emergency window is extended, and the corresponding leakage risk is reduced. In addition, the leakage rate of crude oil is slower than that of diesel oil. After 850 days of downward migration of approximately 190 m, the pollutant reaches quasi-static equilibrium in the big sand ditch. The results of the surface water oil spill analysis demonstrated that the oil film on the river surface migrated for 100 min after the spill, with a thickness that remained between 0.02 and 0.05 mm and a concentration that approached equilibrium.